Changing regulation and the future of the professional partnership: the case of the Legal Services Act, 2007 in England and Wales. Issue 3 (1st September 2016) - Aulakh, Sundeep; Kirkpatrick, Ian
ABSTRACT: The UK Legal Services Act 2007 permits external financing and unlimited non-lawyer ownership of legal practices through the formation of Alternative Business Structures (ABSs). For many, the impact of this changed regulation on the 'professional partnership', as the dominant organisational form through which legal services are delivered, will be considerable. However, to date few studies have explored this empirically. This paper addresses this gap by examining organisational changes within ABSs to assess how far these firms have departed from the professional partnership model. Focusing upon the ABS population licensed by the Solicitors Regulation Authority between January 2012 and August 2015, the study findings show a continuum of organisational responses against four specified indicators: incorporation; multi-disciplinary practices; non-lawyer ownership; and external investment. These range from those that depart little from traditional practices to those that are more radical. We conclude that, whilst regulatory reform has yet to dislodge the dominance of the professional partnership, it has disturbed the status quo and increased the variety of 'economic units' within which legal services are delivered.